On asymptotics of the entropy estimator variance for symmetric Bernoulli measures - E. A. Timofeev (Моделирование и анализ информационных систем, 2009)
We consider Bernoulli measures with equally probable symbols and obtain a closed-form expression of the Grassberger entropy estimator variance.